2009
DOI: 10.21608/jacb.2009.99270
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Fiber Quality Potential for Triallel Crosses in Cotton: 2- Superiority

Abstract: In this study five varieties were used. These varieties were Suvin (P1), TNB (P2), Pima S6 (P3), G. 88 (P4) and G. 89 (P5). The all possible crosses among the three parental varieties to form 30 three way crosses. All genetic materials (five parental varieties, 30 three-way crosses, 10 F1 single crosses and two check varieties) were evaluated at Sakha Agriculture Research Station. Heterosis (Superiority) at Mid-parents, better parent, mid-F1 single crosses, better F1 single crosses, mid-checks and better check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Thus, it can be concluded that the parents possessing only high values need not necessarily produce high yielding hybrids as indicated by the present study, Yehia, et al [36] and El-Hashash [8] and Sorour et al [33] reported that some crosses exhibited significant or highly significant positive heterosis over midparents for yield, yield components and fiber traits, While, the heterosis over better parent exhibited insignificant positive and desirable for all studied traits. The significant negative heterosis suggested the importance of additive genetic components EL-Hashash [8] and Yehia and EL-Hashash [31].…”
Section: Discussionsupporting
confidence: 59%
“…Thus, it can be concluded that the parents possessing only high values need not necessarily produce high yielding hybrids as indicated by the present study, Yehia, et al [36] and El-Hashash [8] and Sorour et al [33] reported that some crosses exhibited significant or highly significant positive heterosis over midparents for yield, yield components and fiber traits, While, the heterosis over better parent exhibited insignificant positive and desirable for all studied traits. The significant negative heterosis suggested the importance of additive genetic components EL-Hashash [8] and Yehia and EL-Hashash [31].…”
Section: Discussionsupporting
confidence: 59%
“…Consequently, the parents involved in the TNB x G. 94, (G.90x Aus.12) x G.86 and G.96 x G.94 combinations should be used in improving yield, its components and fiber quality traits, and the best crosses should be used in initiating the breeding program in Egypt. Some F1 hybrids reflected desirable (positive/negative) heterotic effects for cotton yield, its components, and fiber quality traits when estimated, especially, with the higher parents.The obtained results are consistent with previous findings of (Yehia et al, 2009;and El-Hashash, 2013;Patel and Patel, 2018;Yehia and El-Hashash, 2019;and Mariz et al, 2021) they reported significant heterosis in desired sign and direction for all studied traits in cotton.Based on MPH and BPH, the crosses TNB x G. 94, (G.90x Aus.12) x G.86 and G.96 x G.94 were identified as the best hybrids chosen in the best combination for yield, yield components and fiber quality traits.The preponderance of dominance type of gene actions clearly indicated that the selection of superior plants should be postponed to the next generations. The significant negative heterosis suggested the importance of additive genetic components (Muhammed et al, 2003;El-Hashash, 2013).…”
Section: Discussionsupporting
confidence: 92%